Discogenic lower back pain: Current concepts. (July 2014) - Inklebarger, James
<x content-type="archive" xml:space="preserve">Abstract</x> The literature reports that 39% of chronic lower back pain may be attributed to intervertebral disc derangement. However, definitive diagnosis of discogenic lower back pain (DLBP) remains challenging. Clinical examination may be normal and the correlative utility of magnetic resonance imaging findings such as the high intensity zone is controversial. Researchers have identified a complex interplay of degenerative, immunohistological, and biomechanical overload factors as causative. Due to difficulties in diagnosis through physical examination and imaging alone, provocative discography is still the gold standard for surgical planning, by measuring intradiscal pressure, finding extradiscal dye extravasation, and by reproducing concordant pain against controls. This remains so, despite the known sequelae of latent acceleration of disc degeneration following the procedure. Lumbar interbody fusion (LIF), in its various forms, is the traditional surgical management for intractable pain from DLBP. However, due to this surgery's known complications of progressive biomechanical overload and degeneration of adjacent non-fused segments, it is regarded as an end of the line management. Artificial disc implants may offer an improved biomechanical alternative to LIF, but its efficacy is uncertain; while new non-surgical managements, such as stem cell regeneration and gene therapy, show promise but require further investigation. This paper explores some of the research opinions, theories of causation, and management strategies.